Cerita Dhampu Awang dalam Naskah Nyi Junti: Mengurai Hubungan Indramayu dan Tionghoa pada Abad ke-15 - Nurhata Nurhata (IAIN Syekh Nurjati Cirebon, 2022)
The story of Dhampu Awang or known as Ma Huan is very popular among the coastal community groups of Indramayu. Traces of the past associated with Dhampu Awang can be traced from ancient sites, oral traditions, and manuscripts. A more specific story about Dhampu Awang is described in the Nyi Junti manuscript. This study describes the traces of the Chinese in Indramayu in the 15th century based on the Tamanan Site (Situs Tamanan), the Dhampu Awang folklore, and the Nyi Junti manuscript. The three sources after the dialogue affirmed each other. After being analyzed, we get a picture of the role of the Chinese in filling the early stages of the development of the Islamic sultanate of Cirebon (15th century), in which Dhampu Awang's position is a key figure. The results of the analysis obtained an overview of the role of the Chinese in filling the development phase of the coastal area of Indramayu, where Dhampu Awang is the key figure. The relationship between the Indramayu community and Chinese immigrants is mutually beneficial, giving a distinct impression, especially for those who live in coastal areas